2012
DOI: 10.1177/1359105312464675
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the mental health care needs and utilization by families of children with a food allergy

Abstract: The present study aimed to examine whether caretakers of children with a food allergy experience distress and to determine their family's mental health-care needs and utilization. An anonymous survey was given to a sample of 454 caretakers during conferences hosted by the Food Allergy & Anaphylaxis Network. Overall, 32 percent of caretakers reported above threshold levels of distress while 70 percent stated that mental health support would have been helpful, but only 23 percent sought it. Even when mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…However, it warrants mention that non-food allergic households reported no such negative events. Elsewhere, Annunziato et al reported that 70% of mothers with food allergic children reported that mental health support would be beneficial 15 . Yet, to our knowledge, these types of sustained supports are not commonly available.…”
Section: Discussionmentioning
confidence: 99%
“…However, it warrants mention that non-food allergic households reported no such negative events. Elsewhere, Annunziato et al reported that 70% of mothers with food allergic children reported that mental health support would be beneficial 15 . Yet, to our knowledge, these types of sustained supports are not commonly available.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of characteristics in the High Responder and Anxious High Responder groups suggests that children and their parents would benefit from behavioral health interventions with goals of processing severe FA reactions, addressing posttraumatic stress disorder symptoms when present, addressing potential cognitive distortions of threat, and improving skills for coping with FA anxiety and day-to-day FA challenges. (3133) For children, assessing and promoting developmentally appropriate self-management capabilities including self-advocacy, symptom awareness, and response readiness may facilitate greater balanced management in the entire family. Families with a Low Responders presentation could benefit from education about FA to increase their general FA knowledge and understanding of FA management principles.…”
Section: Discussionmentioning
confidence: 99%
“…Because psychosocial interventions may be beneficial, the level of caregiver stress is also important to assess. Annunziato et al surveyed mothers attending a food allergy conference, and 70% of them reported that a mental health referral would be helpful [53]. Barriers to receiving mental health care included cost, lack of time, and lack of providers with specific expertise.…”
Section: Mental Health Interventionsmentioning
confidence: 99%